(untitled) (Fiep Bulletin - online, 2014)
According to the World Health Organization (WHO) more than 80% of people feel back pain at some point in their lives. This disease represents a major socioeconomic problem, disabling individuals for the conduct of its activities. The acupuncture promotes reduction of back pain, but its results are still controversial because of the many possibilities for treatment. This study was aimed at comparing the action of acupuncture in the treatment of patients with low back pain by using proximal and distal points in the reduction of pain, through visual analog scale and orthopedic tests of Lasègue and Schober. Twelve volunteers took part of the study and they were divided into two groups with equal numbers of participants. In the group of local treatment, the point B23 was used bilaterally and in the group that received treatment distal the point B60 was used bilateraly. The needles were maintained for 15 minutes and maneuvers of sedation was performed every 5 minutes. The local group of volunteers showed greater reduction in pain and improvement in test Schober, though it remained positive. The test Laségue results presented noticed similar in the two groups and has been fully resolved. We could conclude that the local treatment produced better results than the distal one, but there was reduction of pain and resolution of the Laségue test in both forms of treatment. These results if not probative are highly suggestive of the effectiveness of acupuncture in the treatment of back pain and add knowledge to the existing literature promoting greater knowledge of a technical millenary and that brings many health benefits.